Answer: The correct factors are
(x-1) and (x+2)
Step-by-step explanation:
Step one :
To factorize the equation
x²– x – 2=0
First we look for numbers that when multiplied will result to the constant term and when added will result to the second term (1x, - 2x)
Step two :
We replace the second term with these factors we have
x²–(x-2x)–2=0
x²–x+2x–2=0
Factoring the expression we have
x(x–1)+2(x–1)=0
Hence the factors will be
(x-1) and (x+2)
Answer:
x=3/7
Step-by-step explanation:
x+4 5/7 = 12x
4 5/7 = 11x
x = 3/7
Answer:
a.
and 41.6
b. 52.1
Step-by-step explanation:
a.
Considering the left side triangle the blue dotted side is the side "opposite" to the angle given and the side 24 is the side that is "adjacent" to the angle given. The trigonometric ratio tan relates opposite to adjacent. Also, let the blue dotted side be y.
<u>Note:</u> the exact value of tan 60 is 
Thus, we can write 
Approximate value (rounded to nearest tenth): 
b.
Considering the triangle to the right, the side "opposite" to the angle given (53 degrees) is 41.6 (just found in part (a)) and the side "hypotenuse" (side opposite to 90 degree angle) is x. The trigonometric ratio sine relates opposite and hypotenuse.
Thus we can write and solve:

Answer:
x = 1
Step-by-step explanation:
Our goal is to isolate x on one side. So:
-6 +5x = 6x - 7
-6 = x - 7
1 = x
Hope that helped!
Answer:
your 3rd option
Step-by-step explanation:



